Mortality and Outcomes of Pediatric Tracheostomy Dependent Patients - Hebbar, Kiran B.; Kasi, Ajay S.; Vielkind, Monica; McCracken, Courtney E.; Ivie, Caroline C.; Prickett, Kara K.; Simon, Dawn M. (Frontiers in Pediatrics, 2021)
Objective: To describe clinical factors associated with mortality and causes of death in tracheostomy-dependent (TD) children. Methods: A retrospective study of patients with a new or established tracheostomy requiring hospitalization at a large tertiary children’s hospital between 2009 and 2015 was conducted. Patient groups were developed based on indication for tracheostomy: pulmonary, anatomic/airway obstruction, and neurologic causes. The outcome measures were overall mortality rate, mortality risk factors, and causes of death. Results: A total of 187 patients were identified as TD with complete data available for 164 patients. Primary indications for tracheostomy included pulmonary (40%), anatomic/airway obstruction (36%), and neurologic (24%). The median age at tracheostomy and duration of follow up were 6.6 months (IQR 3.5-19.5 months) and 23.8 months (IQR 9.9–46.7 months), respectively. Overall, 45 (27%) patients died during the study period and the median time to death following tracheostomy was 9.8 months (IQR 6.1–29.7 months). Overall survival at 1- and 5-years following tracheostomy was 83% (95% CI:76-88%) and 68% (95% CI:57-76%), respectively. There was no significant difference in mortality based on indication for tracheostomy (p=0.35), however pulmonary indication for tracheostomy was associated with a shorter time to death (HR:1.9; 95%CI:1.04-3.4; p=0.04). Among the co-morbid medical conditions, children with seizure disorder had higher mortality (p=0.04). Conclusion: In this study, TD children had a high mortality rate with no significant difference in mortality based on indication for tracheostomy. Pulmonary indication for tracheostomy was associated with a shorter time to death and neurologic indication was associated with lower decannulation rates.